2002
DOI: 10.1097/00000637-200212000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Growth Factors on Doxorubicin-Induced Skin Necrosis: Documentation of Histomorphological Alterations and Early Treatment by GM-CSF and G-CSF

Abstract: Extravasation of vesicant antineoplastic agents such as doxorubicin into the skin or subcutaneous tissues may result in loss of the full thickness of the skin or underlying structures. Several treatment methods have been advocated but none has demonstrated any superiority to the others. The authors designed a controlled animal study in 88 rats to test three methods of early treatment of extravasation of the vesicant antineoplastic agent doxorubicin. The first step of the study included 48 Sprague-Dawley rats. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…9,14 However, no agent could be suggested for clinic use. Thus, we evaluated the effects of carnitine, a potent antioxidant, on doxorubicin induced extravasation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…9,14 However, no agent could be suggested for clinic use. Thus, we evaluated the effects of carnitine, a potent antioxidant, on doxorubicin induced extravasation.…”
Section: Resultsmentioning
confidence: 99%
“…All these agents has different effect mechanisms such as scavenging free oxygen radicals, reducing inflamatory responce, increasing new vessles , inhibiting coagulation, increasing endothelial cell proliferation and angiogenesis. 6,8,15,16 Several clinical and surgical approaches have been tested as well such as VAC, hyperbaric oxygen therapy and surgical intervention. [17][18][19] We tested carnitine for doxorubicin induced extravasation injuries in our study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…21 It is well known that G-CSF contributes to the healing of myocardial infarction, 7 diabetic ulcers of the skin, 22 and ischemic necrosis resulting from doxorubicin extravasation. 23,24 A recent study also demonstrated that intramuscular injection of G-CSF induced angiogenesis through mechanisms independent of EPC mobilization. 25 These findings suggest that other possible mechanisms of G-CSF, such as direct angiogenesis and wound healing, may play a role.…”
Section: Mechanisms Of G-csf Effectmentioning
confidence: 98%
“…However, immediate intervention is indicated in case of non-resolving erythema, pain or swelling and presence of large skin defects. Few experimental animal and human studies have reported good results with the use of granulocyte macrophage colony stimulating factor (GM-CSF) in the management of ulcers in anthracycline extravasation 19,[56][57][58][59] .…”
mentioning
confidence: 99%